Pengaruh Efikasi Diri, Dukungan Keluarga dan Pendidikan Kewirausahaan terhadap Minat Berwirausaha Mahasiswa - Fauziah, Yovi Noor; Suherti, Heti; Gumilar, Rendra (Global Education Journal, 2023)
Unemployment among educated people makes a significant contribution. One of the triggers is the low interest in entrepreneurship among students. This is indicated by students' low participation in activities related to entrepreneurship since they were in college. After graduation, students prefer careers as employees or civil servants rather than entrepreneurs. This study aims to determine the extent to which self-efficacy, family support, and entrepreneurship education affect the interest in entrepreneurship either simultaneously or partially. This study uses a quantitative survey method with an explanatory survey design. The research population is students of the Department of Economics Education, Siliwangi University, Class of 2020. The sampling technique is saturated sampling, which totals 112 students. The data collection technique uses a questionnaire, and the data analysis technique uses the SPSS 25.0 for Windows program. The results showed: 1) There is a significant influence between self-efficacy on the interest in entrepreneurship with a significance value of 0.030; 2) There is no significant effect between family support on the interest in entrepreneurship with a significance value of 0.405; 3) There is no significant effect between entrepreneurship education on interest in entrepreneurship with a significance value of 0.321 4) There is a significant influence between self-efficacy, family support and entrepreneurship education on interest in entrepreneurship with a significance value of 0.000.